BS EN IEC 61753-021-02. Fibre optic interconnecting devices and passive components. Performance standard. Part 021-02. Single-mode fibre optic connectors terminated as pigtails and patchcords for category C. Controlled environment (14th January 2022) - British Standards Institution,
No abstract available